Micropropagation of Vitex spp. through in vitro manipulation: Current status and future prospectives - Ahmad, Naseem; Shahid, Afsheen; Javed, Saad Bin; Khan, Md. Imran; Anis, Mohammad (Journal of applied research on medicinal and aromatic plants, 2015)
[Display omitted] •Vitex species are widely used in various pharmacopeia.•Harvesting from the wild is threatening its existence.•Biotechnological interventions help in restoration of the genus.•Recommendations for sustainable utilization and future prospects are highlighted. The genus Vitex belonging to family Verbenaceae possesses diverse medicinal properties ranging from anti-inflammatory, anti-allergic, anti-microbial to anti-cancer and anti-HIV. Many potential bioactive molecules form an integral part, of which some are highly valued by multinational pharmaceutical companies. Unrestricted harvesting and high market demand of many medicinal plants including Vitex had drastically reduced the existing wild stocks, a concern that needs attention. Such practices necessitate the intervention of biotechnological techniques such as plant tissue culture for mass propagation and conservation of this valuable genus. Micropropagation, a key tissue culture technique provides new vistas for the conservation of many important plant species. In recent years, various researches dealing with micropropagation of medicinal plants have come forth to take up the challenge. A careful and judicious approach in selecting the right combinations of various factors plays an important role in determining the fate of the regeneration pathway. Present day knowledge on different strategies dealing with micropropagation and in vitro conservation of various species of Vitex are a subject of discussion in the present review. Moreover, role of different factors like type of plant growth regulators and additives, their dosages, explant types, etc., in developing an efficient regeneration system for the genus is discussed.